Investigation of imaging magnification in radiostereometric analysis. (January 2017) - Broberg, Jordan S; Yuan, Xunhua; Teeter, Matthew G
Radiostereometric analysis is a highly accurate imaging technique. A recent advance in radiostereometric analysis is the use of flat panel digital radiography, which provides the opportunity for quick analysis using radiostereometric analysis. However, such a setup is expensive. Using large cassettes for small joints could minimize the cost. In this article, we investigated the influence of cassette size for small joint examinations with a biplanar radiostereometric analysis setup. Our results indicated that there is no significant difference in the precision when using large cassettes over small cassettes, whether or not imaging magnification is applied.